Dinâmica da população de Scleronema micranthum Ducke em uma floresta de terra firme, Manaus – Amazonas - Leitão, Klinger Renasson Pereira (Instituto Nacional de Pesquisas da Amazônia - INPA, 2014)
The objective of this study was to evaluate the population dynamics Scleronema micranthum Ducke during the period from 1996 to 2013, according to an environmental gradient and check possible variations are explained by means of leaf traits. The study was conducted on two transects of 20x2500 m (5 hectares) each, oriented in the East-West and North-South directions, at km 23 of the outer ZF-2 which starts at km 50 of BR-174 (Manaus-AM). We selected individuals of S. micranthum with DBH≥10 cm, and stratified into different topographic classes and different classes of crown exposure to sunlight. Stratification in topographic classes (plateau, slope and valley) was used to evaluate the difference in population dynamics and functional traits. The crown exposure classes to incidence of sunlight (emergent, canopy primary, secondary canopy and understory) was used to evaluate only the variation of functional traits. Population dynamics as the periodic annual increment in DBH (PAIDBH), absolute dominance (AD), and annual rates of recruitment (R%) and mortality (M%) were based on measurements made in eight census intervals [1996, 2000, 2002, 2004, 2006, 2008, 2010, 2011, 2013]. The leaves of the individuals were collected in 2013 and the following functional traits were analyzed: specific leaf area (SLA), leaf toughness and ratio of carbon and nitrogen (C:N). The topographic gradient did not influence PAIDBH and functional traits, however can influence the R%, M% and DA. The main variation occurs in traces changes in canopy exposure to irradiation. SLA, tenacity and C:N ratio were correlated with each other, but were not correlated with individuals PAIDBH.
Keywords: Scleronema micranthum Ducke; Dinâmica florestal; Traços foliares